Collaborative Governance dalam Program Rehabilitasi Sosial Rumah Tidak Layak Huni di Kota Surabaya - Kristin, Citra; Wibawani, Sri (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
Abstract:  The Social Rehabilitation Program for Uninhabitable Houses abbreviated as rutilahu is a program to improve the quality of housing through repairs as a whole and/or entirely with the principles of acceptability, transparency, accountability, integration, partnership, solidarity, benefits and participation. This study aims to describe in depth the process of collaborative governance in the Social Rehabilitation Program for Uninhabitable Houses in the City of Surabaya. This type of research uses descriptive qualitative techniques with the determining informants through purposive and snowball sampling techniques. Data collection techniques used were observations, interviews, and documentation. Data analysis techniques using "interactive model of analysis" by Miles and Huberman (2014). The collaborative governance process is analyzed by theory (Ansell & Gash, 2007) including face to face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. The results showed that the collaboration process had been successfully carried out at the face to face dialogue, trust building, share understanding, and intermediate outcome stages between the DPRKPP of Surabaya City with BP2P Jawa IV, Baznas Surabaya, YMI ITS, Victory Community Church of Surabaya, KTPR, Bank Mandiri, and from private donor. Meanwhile, the collaboration process at the commitment to the process stage has been quite successful between the parties. In the commitment to the process stage, the majority of the collaborating or participating parties do not yet have written documents that can strengthen their collaborative relationship, so at least a letter of agreement is needed stating or known by the parties concerned.